Graphene aerogel coated with silicon dioxide nano ceramic membrane on surface as well as preparation method and application of graphene aerogel

By coating the silica nanoceramic film on the surface of the graphene aerogel, the problems of high density and low elastic compression strain when improving high temperature resistance are solved, the characteristics of low density, high conductivity and high elasticity are achieved, and its application temperature in high temperature environments is broadened.

CN119551667APending Publication Date: 2025-03-04LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411758319.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

While improving high temperature resistance, the existing graphene aerogels have high density and low elastic compression strain, which limits their application in high temperature environments.

Method used

By coating the silica nanoceramic film on the surface of graphene aerogel, using liquid phase coating technology and high-temperature calcination treatment, a smooth silicon-based coating is formed and cracked at high temperature into a silica nanoceramic film, enhancing its high-temperature oxidation resistance.

Benefits of technology

The low density, high conductivity and high elasticity of graphene aerogel are achieved, and the structure is stable in a high temperature environment of 700℃ for 30 minutes, broadening its application temperature range in the field of pressure sensing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551667A_ABST
    Figure CN119551667A_ABST
Patent Text Reader

Abstract

The invention discloses graphene aerogel coated with a silicon dioxide nano ceramic membrane on the surface and a preparation method and application of the graphene aerogel. The method comprises the steps that graphene oxide aerogel is soaked in an alcohol-water solution of organic silicon, the hydrolytic condensation rate of the organic silicon is adjusted by controlling the pH value and the water content, and the silicon dioxide nano ceramic membrane is obtained. A smooth coating can be formed on the surface of the graphene oxide aerogel; after hydrolytic condensation is completed, reducing the graphene oxide aerogel into graphene aerogel through chemical reduction, and performing high-temperature calcination in an inert atmosphere to perform high-temperature cracking on the silicon-based coating on the surface into a silicon dioxide nano ceramic film, so as to obtain graphene aerogel coated with the silicon dioxide nano ceramic film on the surface; wherein the inert atmosphere high-temperature calcination comprises two stages of calcination processes. The method provided by the invention not only can improve the high-temperature oxidation resistance of the graphene aerogel, but also keeps the characteristics of low density, high conductivity and high elasticity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a graphene aerogel, in particular to a graphene aerogel with a silicon dioxide nano-ceramic film coated on the surface thereof, and a preparation method and application thereof. Background Art

[0002] The information provided in this section is for the purpose of generally presenting the background of the present disclosure. To the extent described in this section, the work of the presently named inventors and aspects of the description that may not constitute prior art at the time of filing are neither explicitly nor implicitly admitted to be prior art to the present disclosure.

[0003] As a two-dimensional material that has attracted much attention, graphene is often assembled into various macroscopic forms for use. Among them, graphene aerogel is a three-dimensional porous foam material constructed by overlapping graphene nanosheets, which has the characteristics of low density, high elasticity and high conductivity. The porous structure of graphene aerogel enables it to deform under slight pressure stimulation and induce changes in resistance, thereby converting external pressure stimulation into electrical signals. Therefore, graphene aerogel has great application potential in the field of flexible intelligent sensing.

[0004] Graphene has a theoretical melting point of up to 4300°C and has extremely excellent thermal stability. However, it is easily corroded by oxygen atoms under high temperature conditions. Oxygen atoms adsorb on graphene nanosheets to form CO or CO2, which destroys and collapses the skeleton of graphene nanosheets (Applied Physics Letters, 2019, 114 (12): 123104). In the atmospheric environment, most of the graphene aerogels reported so far begin to oxidatively decompose above 350°C, which seriously damages the structure of the graphene aerogel, accompanied by a significant decrease or even disappearance of elasticity and conductivity. This greatly limits the application of graphene aerogels in pressure sensing in oxygen-rich high-temperature environments (ACS Applied Materials & Interfaces, 2023, 15 (15): 19337-48).

[0005] Chinese invention patent CN202010865954.4 discloses a high-temperature resistant elastic graphene aerogel and a preparation method thereof. A new type of graphene aerogel is prepared by mixing silica sol with graphene oxide and performing a hydrothermal reduction reaction, and then freeze-drying. The pore walls of this aerogel are loaded with SiO2 nanoparticles. The presence of these nanoparticles enables the graphene aerogel to remain stable in an aerobic environment at 800°C for a short time (10 minutes). However, due to the need to load a large amount of SiO2 nanoparticles on the surface of the aerogel skeleton, the density of this composite aerogel is relatively high (20-60 mg / cm 3), and its elastic compression strain is only 30%. Summary of the invention

[0006] The purpose of the present invention is to provide a graphene aerogel coated with a silicon dioxide nano-ceramic film on the surface, and a preparation method and application thereof, which solves the problem that the prior art improves the high temperature resistance of the graphene aerogel while also causing the density of the composite aerogel to be relatively high and the elastic compression strain to be low. It can not only improve the high temperature oxidation resistance of the graphene aerogel, but also maintain the characteristics of low density, high conductivity and high elasticity.

[0007] In order to achieve the above-mentioned object, the present invention provides a method for preparing a graphene aerogel coated with a silicon dioxide nano-ceramic film on the surface, the method comprising: immersing the graphene oxide aerogel in an alcohol aqueous solution of organic silicon (alcohol as a solvent, water as a reaction initiator), adjusting the organic silicon to catalyze hydrolysis and condensation reaction under acidic conditions by controlling the pH value and water content, so that a smooth coating can be formed on the surface of the graphene oxide aerogel; wherein the volume fraction of the organic silicon is 0.5-10%; the pH value is 4-5; after the hydrolysis and condensation are completed, After that, the graphene oxide aerogel is reduced into graphene aerogel by chemical reduction, and then the silicon-based coating on the surface is cracked into a silicon dioxide nano-ceramic film by high-temperature calcination in an inert atmosphere, so as to obtain the graphene aerogel with the silicon dioxide nano-ceramic film coated on the surface; wherein the inert atmosphere high-temperature calcination includes two calcination processes: the first calcination, heating to 500°C and keeping the temperature for a period of time; the second calcination, heating to 600°C to 1600°C and keeping the temperature for a period of time; and the heating rate of the second calcination is greater than the heating rate of the first calcination.

[0008] In the method of the present invention, if the heating rate is too fast during the calcination process, the reduction process will be too violent, destroying the aerogel structure; if the heating rate is too slow, the aerogel structure will disintegrate under long-term high temperature. Therefore, the present invention solves this problem by combining slow and fast two-stage calcination.

[0009] It should be noted that the second stage of calcination is heated to 600°C to 1400°C, for example, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, 1450°C, 1500°C, 1550°C, and 1600°C for calcination. Only some temperatures that can be used in the present invention are listed here. In addition to these temperatures, it can also be carried out at other temperatures, and the temperature can be achieved between 600°C and 1600°C; preferably, the temperature of the second stage of calcination is between 600°C and 1400°C; more preferably, the temperature of the second stage of calcination is between 1000°C and 1400°C.

[0010] Preferably, the first stage of the high-temperature calcination in the inert atmosphere is heated to 500°C at a heating rate of 2-4°C / min; or / and the second stage of the high-temperature calcination in the inert atmosphere is heated to 600°C-1600°C at a heating rate of 7-10°C / min.

[0011] More preferably, in the first stage of the high-temperature calcination in an inert atmosphere, the temperature is increased to 500°C at a heating rate of 2 to 4°C / min and maintained for 2 hours; or / and in the second stage of the high-temperature calcination in an inert atmosphere, the temperature is increased to 600°C to 1600°C at a heating rate of 7 to 10°C / min and maintained for 2 hours.

[0012] Preferably, the organosilicon is selected from silicate compounds and / or silane compounds.

[0013] Preferably, the silicate compound is selected from at least one of methyl silicate and ethyl silicate; or / and, the silane compound is selected from at least one of triaminopropyltriethoxysilane, methyltrimethoxysilane, vinyltriethoxysilane, triethoxychlorosilane, trimethoxypropylsilane, N-aminoethyl-γ-aminopropyltrimethoxysilane, and 3-(2-aminoethylamino)propylmethyldimethoxysilane.

[0014] Preferably, in the alcohol aqueous solution, the alcohol is selected from at least one of methanol, ethanol, isopropanol and n-propanol; or / and, in the alcohol aqueous solution, the volume ratio of alcohol to water is 4:1 to 1.5.

[0015] Preferably, the reducing agent used in the chemical reduction is selected from at least one of vitamin C, hydroiodic acid, hydrazine hydrate, and ethylenediamine; or / and, the mass fraction of the reducing agent used in the chemical reduction is 3 to 10 wt%; or / and, the reducing agent is prepared with water or ethanol or a mixed solution thereof; or / and, the reduction temperature of the chemical reduction is 60 to 90° C.; or / and, the reduction time of the chemical reduction is 1 to 6 hours; or / and, after the residual reducing agent is cleaned, it is freeze-dried in a freeze dryer for 24 hours; or / and, the graphene oxide aerogel is prepared by ice crystal casting or ion gel method.

[0016] Preferably, the preparation of the graphene oxide aerogel comprises: freezing the graphene oxide aqueous solution in a low temperature environment below -30°C, and then placing it in a freeze dryer for freezing for more than 24 hours to obtain the graphene oxide aerogel.

[0017] Preferably, in the preparation of the graphene oxide aerogel, the concentration of the graphene oxide aqueous solution is 8 to 20 mg / mL. The higher the graphene oxide concentration, the greater the density of the prepared graphene oxide aerogel. Since subsequent operations need to be performed in an ethanol / water solution, the aerogel density is too low to resist the erosion of solvent molecules, and the aerogel as a whole will decompose, so the minimum concentration is 8 mg / mL.

[0018] Another object of the present invention is to provide a graphene aerogel with a silicon dioxide nano-ceramic film coated on the surface obtained by the preparation method.

[0019] Another object of the present invention is to provide the application of the graphene aerogel with the surface coated with a silicon dioxide nano-ceramic film in the field of piezoresistive sensing.

[0020] The graphene aerogel coated with a silicon dioxide nano-ceramic film on the surface of the present invention and the preparation method and application thereof solve the problem that the prior art improves the high temperature resistance of the graphene aerogel while also causing the density of the composite aerogel to be relatively high and the elastic compression strain to be low, and has the following advantages:

[0021] (1) The present invention uses liquid phase coating technology to coat a layer of silicon oxide nanofilm only a few nanometers thick on the surface of graphene aerogel. This nanofilm significantly improves the high-temperature oxidation resistance of graphene aerogel, while maintaining its low density, high conductivity and high elasticity. The density of this improved graphene aerogel is as low as 8-10 mg / cm3, the compression strain can reach 80%, and the conductivity is as high as 15S / cm. At the same time, in a high temperature environment of 700°C, the aerogel can maintain structural stability for 30 minutes; and at 500°C, its structure and mechanical properties can remain stable for more than 2 hours. This significant improvement in performance has broadened the application temperature of graphene aerogel in the field of pressure sensing;

[0022] (2) The method of the present invention uses graphene oxide aqueous dispersion as raw material, adopts traditional methods such as ice crystal casting or ion gel, and combines freeze-drying technology to prepare graphene oxide aerogel; disperses organic silicon in an alcohol aqueous solution, and immerses the graphene oxide aerogel therein; controls the pH value and water content to adjust the catalytic hydrolysis and condensation reaction of organic silicon molecules under acidic conditions so that a smooth coating can be formed on the surface of the graphene oxide aerogel; combines chemical reduction and high-temperature calcination to obtain a graphene aerogel coated with a silicon dioxide nano-ceramic film on the surface. The graphene aerogel obtained by this method can not only improve the high-temperature antioxidant ability of the graphene aerogel, but also maintain the characteristics of low density, high conductivity and high elasticity;

[0023] (3) The method of the present invention improves the high-temperature oxidation resistance and electrical conductivity of the graphene aerogel coated with a silicon dioxide nano-ceramic film on the surface by controlling the amount of organic silicon used and the high-temperature calcination speed in two stages. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 These are morphological photographs of sample (a) of comparative example 2 and sample (b) of example 8 of the present invention before and after calcination in a muffle furnace in an air atmosphere.

[0025] Figure 2 This is an electron microscope photograph of the graphene aerogel with a silicon dioxide nano-ceramic film coated on the surface prepared in Example 2 of the present invention.

[0026] Figure 3 1 and 10 are stress-strain curves of sample (a) of comparative example 3 and sample (b) of example 8 of the present invention.

[0027] Figure 4 Schematic diagram of sensor assembly in Experimental Example 2 of the present invention (a); stress-strain curve of the sample prepared in Example 8 after calcination in an air atmosphere at 500°C for 2h (b); and current change curve of the sample prepared in Example 8 under different strain conditions tested in an environment of 500°C after being assembled into a sensor (c). DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] It should be noted that if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased from the market.

[0030] In the present invention, all features defined in the form of numerical ranges or percentage ranges, such as values, quantities, contents and concentrations, are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0031] The features mentioned in the present invention can be combined arbitrarily, as long as there is no contradiction in the combination of these features, all possible combinations should be considered as the scope of this specification. Each feature disclosed in the specification can be replaced by any alternative feature that can provide the same, equal or similar purpose. Therefore, unless otherwise specified, the disclosed features are only general examples of equal or similar features.

[0032] The invention provides a graphene aerogel with a silicon dioxide nano-ceramic film coated on the surface and a preparation method thereof. The surface of the graphene oxide aerogel has abundant oxygen-containing functional groups and defects that can serve as reactive active sites, thereby facilitating the adsorption of silane and the growth of silicon oxide. The graphene oxide aerogel is immersed in an alcohol-water solution of organic silicon, and the organic silicon molecules are adsorbed on the surface of the graphene oxide aerogel. Under catalytic conditions (pH value and water molecules), a hydrolysis condensation reaction occurs to form a silicon-based coating on the surface of the graphene oxide aerogel. The graphene oxide aerogel can be reduced to graphene aerogel by chemical reduction and high-temperature calcination in an inert atmosphere, and the silicon-based coating on the surface is simultaneously cracked at high temperature to form a silicon dioxide nano-ceramic film.

[0033] The present invention utilizes the protective effect of the ceramic film to weaken the chemical erosion of oxygen atoms on graphene aerogel at high temperature, thereby improving the high-temperature oxidation resistance of the graphene aerogel, while maintaining the characteristics of low density, high conductivity and high elasticity, thereby expanding the temperature range of application of graphene aerogel in the field of piezoresistive sensing.

[0034] The graphene oxide aerogel of the present invention can be obtained by the following method: firstly, using graphene oxide aqueous dispersion as raw material, adopting ice crystal casting or ion gel and the like, combined with freeze drying technology to prepare graphene oxide aerogel.

[0035] The following is a detailed description of a graphene aerogel having a surface coated with a silicon dioxide nano-ceramic film, a preparation method and an application thereof provided by the present invention through various embodiments, comparative examples and experimental examples.

[0036] Example 1

[0037] A graphene aerogel with a silicon dioxide nano-ceramic film coated on its surface, wherein the preparation method comprises the following steps:

[0038] 1) freezing a graphene oxide aqueous solution with a concentration of 10 mg / mL in a low temperature environment of -30°C, and then freeze-drying it in a freeze dryer for 24 hours to obtain a graphene oxide aerogel;

[0039] 2) Ethanol and water are mixed in a volume ratio of 4:1 to prepare an ethanol aqueous solution, and triaminopropyl triethoxysilane is added to the ethanol aqueous solution, and the volume fraction of triaminopropyl triethoxysilane in the mixed solution is 1%. The pH value is adjusted to 5 by dropping acetic acid, and the graphene oxide aerogel is placed in the above solution and soaked for 48 hours;

[0040] 3) Soaking the aerogel in a 3 wt% HI aqueous solution at 80° C. for 4 h, washing the residual reducing agent with clean water, and then placing the aerogel in a freeze dryer for freeze drying for 24 h;

[0041] 4) Under the protection of argon atmosphere, the first calcination was carried out by heating the temperature to 500°C at a heating rate of 2°C / min and maintaining it for 2 h, and then the second calcination was carried out by heating the temperature to 600°C at a heating rate of 7°C / min and maintaining it for 2 h, thereby obtaining a graphene composite aerogel coated with a nano-silica ceramic film on the surface.

[0042] Example 2

[0043] A graphene aerogel coated with a silicon dioxide nano-ceramic film on the surface, the preparation method of which is basically the same as that of Example 1, except that:

[0044] In step 2), the volume fraction of triaminopropyltriethoxysilane in the mixed solution is 3%.

[0045] See also Figure 2 , is an electron microscope photograph of the aerogel prepared in Example 2 of the present invention, and the porous structure of the graphene aerogel can be seen.

[0046] Example 3

[0047] A graphene aerogel coated with a silicon dioxide nano-ceramic film on the surface, the preparation method of which is basically the same as that of Example 1, except that:

[0048] In step 2), the volume fraction of triaminopropyltriethoxysilane in the mixed solution is 5%.

[0049] Example 4

[0050] A graphene aerogel coated with a silicon dioxide nano-ceramic film on the surface, the preparation method of which is basically the same as that of Example 1, except that:

[0051] In step 4), the second stage calcination temperature is raised to 800°C.

[0052] Example 5

[0053] A graphene aerogel coated with a silicon dioxide nano-ceramic film on the surface, the preparation method of which is basically the same as that of Example 1, except that:

[0054] In step 4), the second stage calcination temperature is raised to 1000°C.

[0055] Example 6

[0056] A graphene aerogel coated with a silicon dioxide nano-ceramic film on the surface, the preparation method of which is basically the same as that of Example 1, except that:

[0057] In step 4), the second stage calcination temperature is raised to 1200°C.

[0058] Example 7

[0059] A graphene aerogel coated with a silicon dioxide nano-ceramic film on the surface, the preparation method of which is basically the same as that of Example 1, except that:

[0060] In step 4), the second stage calcination temperature is raised to 1400°C.

[0061] Example 8

[0062] A graphene aerogel coated with a silicon dioxide nano-ceramic film on the surface, the preparation method of which is basically the same as that of Example 1, except that:

[0063] In step 2), the volume fraction of triaminopropyltriethoxysilane in the mixed solution is 5%;

[0064] In step 4), the second stage calcination temperature is raised to 1400°C.

[0065] Example 9

[0066] A graphene aerogel coated with a silicon dioxide nano-ceramic film on its surface, the preparation method of which is basically the same as that of Example 8, except that:

[0067] In step 1), the graphene oxide concentration used is 8 mg / mL;

[0068] In step 2), the organosilane used is 3-(2-aminoethylamino)propylmethyldimethoxysilane.

[0069] Example 10

[0070] A graphene aerogel coated with a silicon dioxide nano-ceramic film on its surface, the preparation method of which is basically the same as that of Example 9, except that:

[0071] In step 2), the organosilane used is N-aminoethyl-γ-aminopropyltrimethoxysilane.

[0072] Embodiment 11

[0073] A graphene aerogel coated with a silicon dioxide nano-ceramic film on its surface, the preparation method of which is basically the same as that of Example 9, except that:

[0074] In step 2), the volume fraction of triaminopropyltriethoxysilane in the mixed solution is 10%.

[0075] Example 12

[0076] A graphene aerogel coated with a silicon dioxide nano-ceramic film on its surface, the preparation method of which is basically the same as that of Example 9, except that:

[0077] In step 2), ethyl silicate is used as the organosilane.

[0078] Comparative Example 1

[0079] A graphene aerogel, the preparation method of which is substantially the same as that of Example 1, except that:

[0080] Without step 2) of Example 1, a graphene aerogel is prepared.

[0081] Comparative Example 2

[0082] A graphene aerogel, the preparation method of which is substantially the same as that of Example 1, except that:

[0083] Without step 2 of Example 1);

[0084] The second calcination stage of step 4) of Example 1 was heated to 1400°C.

[0085] Comparative Example 3

[0086] A graphene / silicon dioxide composite aerogel, the preparation method of which adopts a traditional mixed gel method, and the silicon source adopts silica sol, as follows:

[0087] 1) mixing a graphene oxide aqueous solution with a concentration of 10 mg / mL with silica sol, with a mass ratio of graphene oxide to silica sol of 1:6, and gelling at 90°C for 6 hours;

[0088] 2) Freezing the hydrogel in a low temperature environment of -30°C, and then freeze-drying in a freeze dryer for 24 hours;

[0089] 3) The same as step 4) of Example 1, to obtain a graphene / silicon dioxide composite aerogel.

[0090] Experimental Example 1 High temperature antioxidant performance test

[0091] The high temperature antioxidant properties of the samples (aerogels prepared in Examples 1 to 8 and Comparative Examples 1 to 3) were tested using a synchronous thermal analyzer (STA-449C, Netzsch). The samples were heated at a heating rate of 10°C / min in an air atmosphere, and the maximum heating temperature was 900°C. The mass loss temperature of the sample adopted the extrapolated starting temperature, and the data analysis specifications referred to the relevant parts specified in GB / T33O47.1-2016 and JY / T 0589.4-2020. The results are shown in Table 1.

[0092] Table 1 shows the high temperature antioxidant performance test results of Comparative Examples 1 to 3 and Examples 1 to 12 of the present invention.

[0093]

[0094]

[0095] Note: Density is measured by analytical balance; conductivity is measured by four-probe method; compressible strain is measured by universal testing machine.

[0096] 1) Comparison of Examples 1 to 12 of the present invention and Comparative Examples 1 to 2

[0097] From the results shown in Table 1, although the amount of triaminopropyltriethoxysilane added and the second-stage calcination temperature were different during the reaction, they had no effect on the compressible strain, and the rebound rate could still reach 100% after the strain was compressed by 80%.

[0098] Compared with Examples 1 to 3 of the present invention, as the amount of triaminopropyltriethoxysilane added increases, the conductivity changes, the mass loss starting temperature and the density change slightly, and the high-temperature antioxidant properties are similar.

[0099] Compared with Examples 1, 4 to 7 of the present invention, as the second stage calcination temperature increases, the mass loss starting temperature and the conductivity show an increasing trend, and both change greatly, while the density shows a trend of first increasing and then decreasing, and the change is also small. Obviously, the second stage calcination temperature has a great influence on the high temperature oxidation resistance of the material.

[0100] Compared with Examples 1, 3, 7 and 8 of the present invention, the second stage calcination temperature in Example 8 is changed compared with Example 3, and its mass loss starting temperature is increased by more than 100°C compared with Example 3, and the conductivity is also significantly improved. Example 1 and Example 3, Example 7 and 8 are all increased to the same extent by the amount of triaminopropyltriethoxysilane added, but the mass loss starting temperature of Example 1 and Example 3 is not changed, and the conductivity changes less than that of Examples 7 and 8, and the mass loss starting temperature of Examples 7 and 8 is also improved to a certain extent, indicating that the amount of triaminopropyltriethoxysilane added and the second stage calcination temperature affect each other's high temperature oxidation resistance and conductivity of the material, and there is a synergistic effect between the two influencing factors.

[0101] Compared with Examples 9 to 10 and 12 of the present invention, different organosilanes have a greater influence on density and conductivity.

[0102] Compared with Example 11, in Example 7 of the present invention, the change in graphene oxide concentration has a greater impact on the density. The higher the graphene oxide concentration, the greater the density of the obtained material.

[0103] 2) Compared with pure graphene aerogel

[0104] From the results shown in Table 1, it can be seen that the mass loss temperature of Example 8 is increased by 172°C compared with that of Comparative Example 2.

[0105] In addition, the sample was placed in a muffle furnace and heated at a heating rate of 10 °C / min, and each temperature step was maintained for 30 min. Figure 1 As shown in (a), the sample prepared in Comparative Example 2 is basically decomposed after being heated to 600°C, while the structure of the sample prepared in Example 8 remains intact after being heated to 700°C. This indicates that the high-temperature oxidation resistance of the composite aerogel prepared in the present invention is significantly improved compared with that of pure graphene aerogel.

[0106] 3) Comparison between the present invention and the traditional mixed gel method

[0107] Comparative Example 3 adopts the traditional mixed gel method, and the components are simply mixed and gelled, and then dried to obtain a graphene / silicon dioxide composite aerogel. The present invention coats a layer of silicon dioxide nanofilm on the surface of the graphene aerogel. As shown in Table 1 and Figure 3 As shown, the mass loss temperature, elasticity and conductivity of comparative example 3 are significantly lower than those of the present invention and pure graphene aerogel, while the density is significantly increased. The present invention greatly improves the high temperature oxidation resistance of graphene aerogel while retaining its original low density, high elasticity and high conductivity.

[0108] Experimental Example 2: Sensing Performance Test

[0109] The samples prepared in Example 8 were Figure 4 The structure shown in (a) is assembled into a sensor. The assembled sensor consists of three parts, namely an alumina substrate, gold interdigital electrodes printed on the substrate, and aerogel mounted on the electrodes. The assembled sensor is placed on a 500°C heating plate to test its pressure sensing signal in a high temperature environment.

[0110] The sensor assembled from the sample prepared in Example 8 was placed on a 500°C heating plate to test its pressure sensing signal under high temperature environment. Figure 4 (b) is a stress-strain curve in the compressive strain range of 0 to 50%. The mechanical properties of the sample prepared in Example 8 did not decay at all after being calcined at 500° C. in air atmosphere for 2 hours.

[0111] The sensor assembled from the sample prepared in Example 8 was placed on a 500°C heating plate to test its pressure sensing signal under high temperature environment. Figure 4 As shown in (c), the sensor outputs stable step signals under different strain conditions (the different compressive strains corresponding to the aerogel-assembled sensor are 5%, 10%, 30%, and 60%), showing excellent application potential of high-temperature pressure sensors.

[0112] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for preparing a graphene aerogel coated with a silicon dioxide nano-ceramic film on the surface, characterized in that: The method includes: The graphene oxide aerogel is immersed in an alcohol-water solution of organic silicon, and the organic silicon is regulated to undergo a catalytic hydrolysis and condensation reaction under acidic conditions by controlling the pH value and the water content, so that a smooth coating can be formed on the surface of the graphene oxide aerogel; wherein the volume fraction of the organic silicon is 0.5 to 10%; and the pH value is 4 to 5; After the hydrolysis and condensation are completed, the graphene oxide aerogel is reduced to graphene aerogel by chemical reduction, and then the silicon-based coating on the surface is cracked into a silicon dioxide nano-ceramic film by high-temperature calcination in an inert atmosphere, so as to obtain the graphene aerogel with the silicon dioxide nano-ceramic film coated on the surface; wherein the inert atmosphere high-temperature calcination includes two calcination processes: In the first stage of calcination, the temperature is raised to 500°C and kept at this temperature for a while; The second stage of calcination is to raise the temperature to 600℃~1600℃ and keep it warm for a while; Moreover, the heating rate of the second stage calcination is greater than the heating rate of the first stage calcination.

2. The preparation method according to claim 1, characterized in that: The inert atmosphere high temperature calcination, the first stage of calcination, is heated to 500°C at a heating rate of 2-4°C / min; Or / and, the high temperature calcination in the inert atmosphere, the second stage of calcination, the temperature is increased to 600°C to 1600°C at a heating rate of 7 to 10°C / min.

3. The preparation method according to claim 1, characterized in that: The organosilicon is selected from silicate compounds and / or silane compounds.

4. The preparation method according to claim 3, characterized in that: The silicate compound is selected from at least one of methyl silicate and ethyl silicate; Or / and, the silane compound is selected from at least one of triaminopropyltriethoxysilane, methyltrimethoxysilane, vinyltriethoxysilane, triethoxychlorosilane, trimethoxypropylsilane, N-aminoethyl-γ-aminopropyltrimethoxysilane, and 3-(2-aminoethylamino)propylmethyldimethoxysilane.

5. The preparation method according to claim 1, characterized in that: In the alcohol aqueous solution, the alcohol is selected from at least one of methanol, ethanol, isopropanol and n-propanol; Or / and, in the alcohol aqueous solution, the volume ratio of alcohol to water is 4:1-1.

5.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The chemical reduction adopts a reducing agent selected from at least one of vitamin C, hydroiodic acid, hydrazine hydrate and ethylenediamine; Or / and, the chemical reduction uses a reducing agent with a mass fraction of 3 to 10 wt%; Or / and, the chemical reduction, the reducing agent is prepared by water or ethanol or a mixed solution thereof; Or / and, the chemical reduction has a reduction temperature of 60 to 90°C; Or / and, the chemical reduction has a reduction time of 1 to 6 hours; or / and, the chemical reduction, cleaning the residual reducing agent and freeze-drying in a freeze dryer for 24 hours; Or / and, the graphene oxide aerogel is prepared by ice crystal casting or ion gel method.

7. The preparation method according to claim 6, characterized in that: The preparation of the graphene oxide aerogel comprises: The graphene oxide aqueous solution is frozen in a low temperature environment below -30°C, and then placed in a freeze dryer for freezing for more than 24 hours to obtain a graphene oxide aerogel.

8. The preparation method according to claim 1, characterized in that: In the preparation of the graphene oxide aerogel, the concentration of the graphene oxide aqueous solution is 8 to 20 mg / mL.

9. Graphene aerogel coated with a silicon dioxide nano-ceramic film on the surface obtained by the preparation method according to any one of claims 1 to 8.

10. Application of the graphene aerogel coated with a silicon dioxide nano-ceramic film on the surface as claimed in claim 9 in the field of piezoresistive sensing.

Citation Information

Patent Citations

  • High-temperature-resistant elastic graphene aerogel and preparation method thereof

    CN111974320A

  • Preparation method of super-hydrophobic graphene aerogel

    CN106744912A

  • Preparation method of reduced graphene oxide-silicon dioxide block aerogel

    CN108083262A

  • Preparation method of dense sintering type composite aluminum nitride ceramics

    CN109761616A

  • Preparation method of graphene composite porous silicon oxide ceramic

    CN116063099A